K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 11 2021

\(\left(x-2\right)^2-x^2-6=15\)

<=>\(x^2-4x+4-x^2-6=15\)

<=>\(-4x=17\)

<=>\(x=\frac{-17}{4}\)

7 tháng 11 2021

x2-4x+4-x2-6-15=0

(x2-x2)+(4-6-15)-4x=0

-17-4x=0

-4x=-17

x=\(\dfrac{17}{4}\)

Vậy x=\(\dfrac{17}{4}\)

4 tháng 11 2021

\(a^2-b^2-a-b=\left(a+b\right)\left(a-b\right)-\left(a+b\right)=\left(a+b\right)\left(a-b-1\right)\)

7 tháng 11 2021

=(a-b)(a+b)-(a+b)

=(a+b)(a-b-1)

4 tháng 11 2021

em mới lớp 5

Hảo cao

@Bảo

#Cafe

5 tháng 11 2021

a) Ta có \(\sin^2\alpha+\cos^2\alpha=1\Rightarrow\cos^2\alpha=1-\sin^2\alpha=1-\left(\frac{1}{4}\right)^2=1-\frac{1}{16}=\frac{15}{16}\)

\(\Rightarrow\cos\alpha=\sqrt{\frac{15}{16}}=\frac{\sqrt{15}}{4}\)

5 tháng 11 2021

liên hợp